Look-ahead Behavior in Food Culture: The Case of Korean Food Buying - Anindita Neng Puspa Dwi Ayuningrum; Yasinta Zulaikha; Mohamed Asmy bin Mohd Thas Thaker; Rosana Eri Puspita (JSW (Jurnal Sosiologi Walisongo), 2022)
The behavior of the Indonesian people to buy traditional Korean food is an interesting topic to study. This study intends to analyze the influence of a person's subjective and objective knowledge and the existence of a halal label on buying behavior of traditional Korean food. The research was conducted using a quantitative approach. Data were collected through an online questionnaire from 100 respondents. The results showed that subjective knowledge about Korean food did not affect the purchase intention of Korean food, while the image of the Korean country affected purchasing of traditional Korean food. Halal label testing as a moderating variable was carried out in this study. Halal label moderates’ knowledge on purchase intention and does not moderate the Korean image of purchase intention. The new thing offered in this research is the discussion about the food-culture invasion that attacks Indonesian.